PENGELOLAAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH ATAS - Fitria i Sumitr; Rohiat Rohiat; Zakaria Zakaria (UNIVERSITAS BENGKULU, 2017)
The objective of this research was to describe the management of guidance and counselling program in public senior high school number 8 in south Bengkulu regency. The method of this research is descriptive qualitative. The conclusion of this research are: 1). the program of guidance and counselling in public senior high school number 8 in south Bengkulu regency is arranged completely, and consist of annual program, semester program, monthy program, weekly program and daily program; 2). the application of guidance and counselling program are consist of some services: orientation, information, placement and distribution, the mastery of content, individual counselling, guidance and counselling in group, consultation, and mediation; 3). the result of program evaluation, there is un complete program is guidance and counselling in group; 4). the follow up of the evaluation result is to complete the program and make priority of the program.